The Degree of Using the Communication Skills with Body Language among Teachers of Basic Education Stage in the Province of Sweida (Damascus University Journal of educational and Psychologyical sciences, 2022)
The research aims to identify the degree of using the communication skills with body language among teachers of the basic education stage in the province of Sweida. The objective is to know the differences in teachers' answers on the search tool depending on the variables (gender, years of teaching experience, and academic qualification).  The sample consisted of (390) male and female teachers , were chosen randomly from the schools of the province of Sweida, and a questionnaire was applied to them using body language communication skills (prepared by the researcher) after verifying its validity and reliability.The results indicated the following:• The presence of an average degree in the use of the skill of communicating with body language among teachers of the basic education stage.• There are statistically significant differences between the average scores of the research sample individuals in their performance on the questionnaire according to the gender variable (male/female) in favor of females.• There are statistically significant differences between the average scores of the research sample individuals in their performance on the questionnaire according to the variable number of years of teaching experience (from 1-5 years/6 years or more) in favor of teachers with years of experience from 6 years or more.There are statistically significant differences between the average scores of the research sample individuals in their performance on the questionnaire according to the scientific qualification variable (university degree/educational qualification diploma) in favor of teachers with an educational qualification diploma.
Keywords: communication skills; body language; teachers